Frequency of in‐hospital adverse outcomes and cost utilization associated with cardiac resynchronization therapy defibrillator implantation in the United States. (6th September 2018) - Patel, Nilay; Viles‐Gonzalez, Juan; Agnihotri, Kanishk; Arora, Shilpkumar; Patel, Nileshkumar J.; Aneja, Ekta; Shah, Mahek; Badheka, Apurva O.; Pothineni, Naga Venkata; Kancharla, Krishna; Mulpuru, Siva; Noseworthy, Peter A.; et al.
Abstract: Background: The utilization of cardiac resynchronization therapy defibrillator (CRT‐D) has increased significantly, since its initial approval for use in selected patients with heart failure. Limited data exist as for current trends in implant‐related in‐hospital complications and cost utilization. The aim of our study was to examine in‐hospital complication rates associated with CRT‐D and their trends over the last decade. Methods and Results: Using the Nationwide Inpatient Sample, we estimated 378 248 CRT‐D procedures from 2003 to 2012. We investigated common complications, including mechanical, cardiovascular, pericardial complications (hemopericardium, cardiac tamponade, or pericardiocentesis), pneumothorax, stroke, vascular complications (consisting of hemorrhage/hematoma, incidents requiring surgical repair, and accidental arterial puncture), and in‐hospital deaths described with CRT‐D, defining them by the validated International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code. Mechanical complications (5.9%) were the commonest, followed by cardiovascular (3.6%), respiratory failure (2.4%), and pneumothorax (1.5%). Age (≥65 years), female gender (OR, 95% CI; P value) (1.08, 1.03‐1.13; 0.001), and the Charlson score ≥3 (1.52, 1.45‐1.60; <0.001) were significantly associated with increased mortality/complications. Conclusions: The overall complication rate in patients undergoing CRT‐D has been increasing in the last decade. Age (≥65), female sex, and the Charlson score ≥3 were associated with higher complications. In patients who underwent CRT‐D implantation, postoperative complications were associated with significant increases in cost.